An Assessment of the Effectiveness and Safety of ULTRACOL100 as a Device for Restoring Skin in the Nasolabial Fold Region - Thuy-Tien Thi Trinh; Pham Ngoc Chien; Linh Thi Thuy Le; Nguyen Ngan-Giang; Pham Thi Nga; Sun-Young Nam; Chan-Yeong Heo (Cosmetics, 2023)
One of the most notable signs of an aging face is the nasolabial folds (NLFs), which often diminish emotional well-being and self-confidence. To address this concern, many people seek solutions to improve their appearance, often turning to fillers. The ULTRACOL100 device, a tissue restoration material, has been previously investigated and shown to exhibit significant efficacy in both in vitro and in vivo studies. In this research, we aim to explore the safety and effectiveness of the clinical trial of ULTRACOL100 in improving the skin in the NLF area over an 8-week observation period. Male and Female adults with nasolabial folds received two injections of ULTRACOL100, with a 4-week interval between treatments, on one side of their faces. On the other side, they received control materials (REJURAN®, JUVELOOK®, or HYRONT®). The assessment of skin improvement in the nasolabial fold area for each subject took place before and four weeks after each application. Various skin parameters, such as roughness, elasticity, moisture, transparency, trans-epidermal water loss, tone, radiance, skin pore size, and skin density, were measured to evaluate the outcomes. The application of the ULTRACOL100 device significantly reduced the skin roughness, the trans-epidermal water loss, and the skin pore size and increased the skin’s elasticity and internal elasticity, as well as the skin’s moisture, transparency, skin tone, radiance, and density. This study comprehensively investigates the effectiveness and safety of the ULTRACOL100 device, comparing it with three commercial products (REJURAN®, JUVELOOK®, and HYRONT®). The ULTRACOL100 device showed comparable performance in improving the appearance of the NLF area among this study subjects.